Effective Treatment of Pharmaceutical Waste Water Through Adsorption Using Sugarcane Bagasse Derived Cellulose Nanocrystal as an Innovative Adsorbent - Hammari, Abubakar M.; Hamza, U. D.; Ibrahim, Maryam; Garba, Kabir; Muhammad, I. M. (Darul Yasin Al Sys, 2025)
This study investigates the production of cellulose nanocrystals (CNCs) from sugarcane bagasse and evaluates their adsorption performance for the removal of metronidazole (MNZ) from aqueous solutions. CNCs were synthesized through acid hydrolysis and characterized for use as an adsorbent. Batch adsorption experiments were conducted to assess the interaction between MNZ and CNCs under varying conditions. Equilibrium data were analyzed using Langmuir and Freundlich isotherm models, with the Freundlich model demonstrating a superior fit (R² = 0.8818), indicating multilayer adsorption on a heterogeneous surface. Kinetic modeling revealed that the adsorption process followed a pseudo-second-order model (R² = 0.9972), suggesting that chemisorption is the dominant mechanism. Thermodynamic parameters, including Gibbs free energy (ΔG), enthalpy (ΔH), and entropy (ΔS), were calculated to understand the nature of the adsorption. Negative ΔG values at all examined temperatures confirmed the spontaneous nature of the process, while positive ΔH values indicated that adsorption was endothermic and favored at elevated temperatures. The results collectively demonstrate that sugarcane bagasse-derived CNCs exhibit promising adsorption capabilities for MNZ, combining favorable kinetics, thermodynamics, and equilibrium behavior. This work underscores the potential of agricultural waste valorization for the development of cost-effective and sustainable adsorbents for pharmaceutical pollutant removal in water treatment applications.